Wavelet Image Compression - Pearlman, William A (San Rafael : Morgan & Claypool Publishers, 2013)
This book explains the stages necessary to create a wavelet compression system for images and describes state-of-the-art systems used in image compression standards and current research. It starts with a high level discussion of the properties of the wavelet transform, especially the decomposition into multi-resolution subbands. It continues with an exposition of the null-zone, uniform quantization used in most subband coding systems and the optimal allocation of bitrate to the different subbands. Then the image compression systems of the FBI Fingerprint Compression Standard and the JPEG2000 S.
Example of SPIHT CodingResolution Scalable SPIHT; Block-Oriented Coding and Random Access Decoding; Embedded Zerotree Wavelet (EZW) Coding; An EZW Coding Example; Rate Control for Embedded Block Coders; Conclusion; Further Reading and Resources; Bibliography; Author's Biography; Index.
Includes bibliographical references and index.
Incudes bibliography : (page 69-75) and index.
Keywords: Image compression; Image processing -- Digital techniques; Wavelets (Mathematics).